The Role of Diabetic Retinopathy Pathogenesis in Diabetic Retinopathy Therapy (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
Introduction: The estimation of diabetes mellitus (DM) patients nowadays are 486 million people. Diabetic retinopathy (DR) serves as one of the most common microvascular disease complications. About 2,6 million people with DM are suffered from visual disturbance. The pathogenesis of DR consists of several mechanisms. These mechanisms are the basics of the DR standard therapies. This review is conducted to observe the pathogenesis of diabetic retinopathy related to the treatment that existed through current literature Methods: An online literature search was conducted in PubMed for relevant publications between 2011 and 2021 by combining the following search terms: retina, diabetic retinopathy, pathogenesis, hyperglycemia, oxidative stress, and management. Results: Retinal neurodegeneration consists of several steps that cause ROS elevation. Retinal microvasculopathy causes increase microvasculature. Chronic inflammation cause progressive damage to the retina. Based on diabetic retinopathy pathogenesis, the therapy includes pharmacological and nonpharmacological treatment. Pharmacological treatment aims to reduce blood glucose and progress through anti-VEGF and anti-inflammatory drugs. Non-pharmacological treatment is the option to treat severe DR and acts as conjunctive therapy towards pharmacological therapy. Conclusions: Based on the current literature, it can be concluded that the pathogenesis of diabetic retinopathy plays an important role in the DR therapy that already existed, especially in the micovasculopathy and inflammation stage..